2008
DOI: 10.1063/1.2964823
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Behavior of a Concentrated Non-Brownian Glass Fiber Suspension in Simple Shear Flow

Abstract: The dynamic behavior of a concentrated short glass fiber suspension subject to simple shear flow is investigated. In particular we are interested in determining the relationship between the stress growth functions (shear and first normal stress difference) and the fiber microstructure within the sample. Stress growth experiments, in start up of flow, are performed on a Rheometrics Mechanical Spectrometer (RMS-800) using a novel approach which deforms the sample in a homogeneous shear field. The 3D fiber orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The hole diameter varied slightly, 23.8 ± 0.5 mm and was accounted for in calculating the stresses for each run. A comprehensive analysis and description of the donut sample can be found elsewhere [16,17].…”
Section: Rheological Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hole diameter varied slightly, 23.8 ± 0.5 mm and was accounted for in calculating the stresses for each run. A comprehensive analysis and description of the donut sample can be found elsewhere [16,17].…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…We do note, however, that the stress growth experiments used in the comparison were performed in a rotational rheometer with parallel disk geometry in which there is a varying shear rate from the center of the plates to the rim. Recent results have suggested that the inhomogeneous shear field in the parallel disk geometry induces excessive fiber-fiber interaction in concentrated fiber suspensions which can have a severe effect on the magnitude of the stress growth overshoot peak and width of the overshoot [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A new set of model parameters was determined by fitting model predictions from rheometrical simulations to orientation data measured on the sheared "donut" sample data of Eberle (2008) assuming that steady state was reached at γ = 50. It should be noticed that γ = 50, is the strain where the orientation data begins to level off.…”
Section: Evolution Of Fiber Orientation and Model Parametersmentioning
confidence: 99%
“…That said, the literature devoted to experimental studies of the rheology of pulp fibres in reinforced polymer composites is very restricted. This is likely due to the complex nature of these materials, the difficulties encountered during their processing as well as the difficulty of characterizing them rheologically [19]- [25].…”
Section: Introductionmentioning
confidence: 99%